SNP Database for Asian wolves - Pilot, Małgorzata; Malewski, Tadeusz; Moura, Andre; Grzybowski, Tomasz; Oleński, Kamil; Ruść, Anna; Kamiński, Stanisław; Fadel, Fernanda; Mills, Daniel; Alagaili, Abdulaziz; Mohammed, Osama; Kłys, Grzegorz; et al. (Dryad Digital Repository, 2015)
Database of SNP genotypes in PLINK format of 79 wolves sampled across Asia